Caracteristicas farmacognósticas y cuantificación de flavonoides totales del fruto de Cyphomandra betacea “tomate de árbol” - Saavedra Gomez, Merly Pamela (2018)
The present study aimed to determine the pharmacognostic study and to quantify the total flavonoids present in the crude extracts, ethanolic and juice of the fruit of Cyphomandra betacea "tomato of tree", whose sample was collected in the district of Lucma, Gran Chimu province. The pharmacognostic study included the determination of macromorphological characteristics, where its weight was determined: 60.38 g and dimensions: width (4.3 cm ± 0.3769), and length: (5.9 cm ± 0.4912); the physicochemical parameters of quality control: foreign matters (0.78%), residual moisture (9.22%), total ash (1.05% ± 0.0816), water-soluble ash (0.49% ± 0.0948) and ash insoluble in acid (0.16% ± 0.0242) and water soluble substances: (6.16% ± 0.7949), ethanol of 50° GL: (5.28% ± 0.2231), ethanol of 70° GL (7.44% ± 0.1271) and ethanol of 96° GL: (7.21% ± 0.0659); which are within the ranges allowed by the pharmacopoeias; also the phytochemical screening "Test of the Drop" was made by Olga Lock. where the presence of phytoconstituents such as polyphenols, flavonoids, triterpenes, leucoanthocyanidins, reducing sugars and saponins. The total Flavonoids quantification was performed by UV-visible spectrophotometry at 256 nm where the crude extract was obtained: 0.0058 (mg / 100g fruit, juice: 0.0604 mg / 100g fruit and ethanol extract: 0.1855 mg / 100g fruit